2015
DOI: 10.5500/wjt.v5.i3.73
|View full text |Cite
|
Sign up to set email alerts
|

Minimizationvstailoring: Where do we stand with personalized immunosuppression during renal transplantation in 2015?

Abstract: The introduction of novel immunosuppressive agents over the last two decades and the improvement of our diagnostic tools for early detection of antibodymediated injury offer us an opportunity, if not a mandate, to better match the immunosuppression needs of the individual patients with side effects of the therapy. However, immunosuppressive regimens in the majority of programs remain mostly protocol-driven, with relatively little inter-program heterogeneity in certain areas of the world. Emerging data showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 59 publications
0
25
0
2
Order By: Relevance
“…It is important to note that a previous study found that kidney transplant recipients who received early corticosteroid withdrawal had a 1.6% reduction in fracture compared to recipients who received standard corticosteroid based immunosuppression [43] . Future studies should explore this further, including measuring glucocorticoid use as a continuous variable and assessing the impact of reduced dose on fracture risk, with a consideration given to the impact this may have on long-term immunological outcomes (e.g., graft loss) [44] . Second, we were unable to assess several risk factors, such as body mass index and estimated glomerular filtration rate, due to a high proportion of missingness (> 50%).…”
Section: Naylor Kl Et Al Fracture Risk Factors In Kidney Transplantmentioning
confidence: 99%
“…It is important to note that a previous study found that kidney transplant recipients who received early corticosteroid withdrawal had a 1.6% reduction in fracture compared to recipients who received standard corticosteroid based immunosuppression [43] . Future studies should explore this further, including measuring glucocorticoid use as a continuous variable and assessing the impact of reduced dose on fracture risk, with a consideration given to the impact this may have on long-term immunological outcomes (e.g., graft loss) [44] . Second, we were unable to assess several risk factors, such as body mass index and estimated glomerular filtration rate, due to a high proportion of missingness (> 50%).…”
Section: Naylor Kl Et Al Fracture Risk Factors In Kidney Transplantmentioning
confidence: 99%
“…Calcineurin inhibitors are associated with an increased risk of hypertension, new‐onset diabetes after transplantation (NODAT), and dyslipidaemia, and are implicated in endothelial dysfunction and GFR impairment . Corticosteroids are associated with dyslipidaemia, NODAT, hypertension, metabolic bone disease, and accelerated atherosclerotic vascular disease …”
Section: Metabolic Complications Of Selected Immunosuppressantsmentioning
confidence: 99%
“…Ami jelenleg biztonsággal kijelenthető, hogy a magasabb kockázatú donorok és recipiensek párosításával végzett veseátültetések eredményei rövid távon nem rosszabbak a korábbi időszakban mért adatokhoz képest, azaz az esetszám biztonsággal növelhető a korábban marginális-nak (ECD) tekintett donorok és nem ideálisnak tartott recipiensek elfogadásával, a megfelelő perioperatív ellá-tás, immunszuppresszió és személyre szabott kezelés mellett [35]. A betegek edukációja, a megfelelő ismeretterjesztés [36] és a nefrológiai ellátásban részt vevő kollégákkal fenntartott, nyílt, konzultatív és konstruktív kapcsolat alapján várható a várólistára referált betegek arányának növekedése a jelenlegi 10-13%-ról akár 20%-ra, az élődonoros program részarányának növekedésével együtt.…”
Section: áBraunclassified